Influência de diferentes ingredientes sobre a qualidade e estabilidade de mortadela conservada a 35°C - Thiel, Suslin Raatz (2018)
Mortadella is one of the most consumed meat products in several countries, its consumption is attributed due to its pleasant taste and low cost. Currently, with changes in Brazilian legislation, industries find it difficult to achieve and maintain the determined value of 0,955 of water activity of products sold at room temperature. Aiming to maintain water activity 0,955, the objective of the present study was to evaluate the effects of different ingredients on water activity and stability of mortadella stored at room temperature. In the preparation of mortadella formulations, the experiment planning methodology was used, where the concentration of maize starch (0, 2,5 and 5%) was varied; concentrated soy protein (0, 1 and 2%); powdered milk (0, 1 and 2%) and crystal sugar (0, 1,5 and 3%). The results indicated that the four ingredients significantly affected (p <0,05) the quality of the products. For moisture the ingredients of soy protein and corn starch presented the greatest effects. For the water activity, the ingredients milk powder and sugar presented greater effects. The results of emulsion stability with heating, milk powder and corn starch presented a significant positive effect, since for emulsion stability without heating the starch did not have the same effect. Losses due to reheating and freezing, with addition of these ingredients there were lower losses, because the ingredients have the capacity to bind the water in the food matrix. The addition of these ingredients represents an alternative for the reduction of water activity with potential application in mortadella marketed at room temperature.